Minidose effect of using acetylsalicylic acid to prevent preeclampsia hospital experience Arzobispo Loayza - Mere, Juan (2015)
Objectives: To determine the effectiveness of low dose salicylic acid acetate (aspirin) in preeclampsia prevention. Design: Clinical randomized trial. Setting: Loayza General Hospital Obstetrical Service. Material and methods: Forty-three primigravidae less than 20 weeks pregnant with hypocalciuria received 100 mg/d of salicylic acid acetate. Other 43 primigravidae with similar clinical characteristics were controls. Results: The incidence of preeclampsia was 16,3% in both groups. Conclusion: The use of low dose salicylic acid acetate did not change the incidence of preeclampsia in this group of patients.